Effect of Arabinoxylan and Arabinogalactan on Textural Attributes of Bread. Issue 6 (29th August 2014) - Saeed, F.; Arshad, M.U.; Pasha, I.; Suleria, H.A.R.; Arshad, M.S.; Qamar, A.; Ullah, Azmat; Sultan, S.
Abstract: In the current research, arabinoxylans (AX) and arabinogalactans (AG) were extracted from different wheat varieties and utilized in bread at different levels (0.5 and 1%). Texture analysis (hardness, fracturability, gumminess, cohesiveness) of dough and bread was performed using texture analyzer. Results showed that the AX content in whole wheat flours ranged from 2.93 to 4.68% while AG ranged from 0.47 to 0.93%. Hardness of bread decreased significantly because of the increase in the levels of AX and AG while it improved during storage study. Moreover, bread fracturability improved as the AX and AG levels increased. Highest gumminess was assigned to Shafaq‐06 with increasing trend from control to 0.5% AX level. After the addition of AG, highest bread gumminess (155.74 ± 6.1, 156.32 ± 7.9) was observed in Shafaq‐06. Both fracturability and gumminess have been increased with the addition of these nonstarch polysaccharides but decreased with the storage intervals. Practical Applications: Arabinoxylan (AX) and arabinogalactan (AG) are of significant importance in that they hold potential in improving the quality of the baked products along with providing health benefits against various ailments. Their role in improving the quality and extending the shelf life of bread by reducing the process of staling and retrogradation is the main idea presented in the article. The dietary fiber is important in this regard and AX and AG contribute significantly to meeting its daily recommendations. These active ingredients possess functional properties that are important for the cereal industry. They enhance the water absorption capacity of the dough thus enhancing the dough development and the dough stability time. They confer viscosity and can increase gas permeability by providing elasticity to protein film surrounding them. Moreover, during bread making they improve the loaf volume, the crumb firmness, reduce retrogradation and indeed enhance the shelf life and storage stability of the bread.